Wage and occupational assimilation by skill level - Miguel Angel Alcobendas; Núria Rodríguez-Planas; Raquel Vegas (Institute for the Study of Labor (IZA), 2012)
While much of the literature on immigrants' assimilation has focused on countries with a large tradition of receiving immigrants and with flexible labor markets, very little is known on how immigrants adjust to other types of host economies. With its severe dual labor market, and an unprecedented immigration boom, Spain presents a quite unique experience to analyze immigrations' assimilation process. Using alternative datasets and methodologies, this paper provides evidence of a differential assimilation pattern for low- versus high-skilled immigrants in Spain: our key finding is that having a high-school degree does not give immigrants an advantage in terms occupational or wage assimilation (relative to their native counterparts).
urn:nbn:de:101:1-201208175125
Keywords: J15; J24; J61; J62; 330; wage assimilation; occupational assimilation; education; Migranten; Qualifikation; Bildungsniveau; Berufliche Integration; Spanien